Performance of Tamil Nadu Tourism Industry - Ganesan, G.; Chandrasekar Rao, K. (Indian Journal of Marketing, 2006)
Tourism is an intensively people oriented industry that is about and of people who move away from home. Tourism rejuvenates people, it changes the outlook of people and also provides livelihood to the host-people. It gives the guests and hosts an opportunity to exchange their cultures. Many of the economies are successful in marketing their country as destinations and generating a substantial amount of foreign exchange from tourism sector. Technology is also playing a big role in the changing dynamics of travel and tourism. Internet has enabled worldwide reach for host of facilities, and enabled rise of new segments such as Free Independent Travelers (FIT), who shun mass tourism packages and set out to explore on their own.